A preliminary study of small field photon dosimetry audits using fabricated Ge-doped optical fibres, TLD-100 and EBT-3 film - Abdullah, N.; Mohd Noor, N.; Wahabi, J.M.; Kamarul Zaman, Z. (Elsevier, 2025)
Preliminary small-field photon dosimetry audits were conducted to evaluate the accuracy of absorbed dose measurements utilising germanium (Ge)-doped optical fibres, both cylindrical (CGedOF) and flat (FGedOF) types, as well as TLD-100, in comparison to the treatment planning system (TPS). Additionally, the dose distribution profiles obtained from the EBT-3 films were assessed. Findings from two radiotherapy centres, covering ten beams, showed that GedOF performed similarly to TLD-100, with the ratio of dosimeter-measured dose to TPS-calculated dose falling within the ±5 % acceptance threshold, suggesting their potential as suitable alternatives for small field dosimetry audits. The beam profile variations for both 2 cm × 5 cm and 2 cm × 2 cm fields at relative doses of 80 %, 50 %, and 20 % were within the 3 mm limit, indicating accurate small field modelling using the TPS. The consistency of results across the two radiotherapy centres implies that the findings are reproducible and could contribute to the establishment of standardised protocols for national small-field dosimetry audits.